Increasing Babesiosis in Southeastern Pennsylvania, 2008–2017. (11th February 2019) - Liu, Hans H; Cushinotto, Lisa; Giger, Olarae; Daum, Gary; McBride, Patricia; Negron, Elizabeth A; Vandegrift, Kurt; Kapelusznik, Luciano
Abstract: Tick-borne illnesses are increasing but are often underreported. Few cases of babesiosis have been reported from Pennsylvania. Our 4-hospital system in southeastern Pennsylvania saw a rise in cases from 7 or fewer yearly in 2008–2014 to 26 cases in 2015. There appear to be multiple potential causes of this increase in frequency.